Thrusting Toward More of the Same with the Porter-McKibbin Report - Calás, Marta B.; Smircich, Linda (Academy of Management Review, 1990)
The article reviews the book ?Management Education & Development: Drift or Thrust Into the 21st Century?? by Lyman Porter and Lawrence McKibbin.